Cetrimonium surfactants with biologically active counter ions as self-immolative drug delivery systems / Syed Waqar Hussain Shah, Iram Bibi and Sabat Yousaf - Hussain Shah, Syed Waqar; Bibi, Iram; Yousaf, Sabat (Universiti Teknologi MARA, 2022)
Novel derivatives of cationic surfactant cetyltrimethylammonium bromide (CTAB) possessing anions of ibuprofen and naproxen as hydrophobic counterions were synthesized and characterized using Fourier transform infrared and differential electronic absorption spectroscopy. The self-assembly of each surfactant was investigated using surface tensiometry. The self-immolative nature of these compounds was analyzed by studying their behaviour in response to a trigger such as medium pH. ADMET-SAR (adsorption, distribution, metabolism, excretion, and toxicity – structure-activity relationship) profiles of synthesized surfactants were generated using admetSAR (v. 1.0). The cetrimonium drugs exhibited better profiles than the corresponding pure drugs, saving the aqueous solubility, which was reduced due to the hydrophobicity of counterions.